Controls on Deposition of the Tordillo Formation in Southern Mendoza (34°–36° S): Implications for the Kimmeridgian Tectonic Setting of the Neuquén Basin - Mescua, Jose Francisco; Suriano, Julieta; Schencman, Laura Jazmín; Giambiagi, Laura Beatriz; Sruoga, Patricia; Balgord, E.; Bechis, Florencia
The Tordillo Formation is a continental succession of red beds deposited in the Neuquén basin during the Kimmeridgian. Based on sedimentological and structural evidence we document an extensional setting between 34˚ and 36˚ S, in the northern part of the basin, which contrasts with a transpressional environment in the Huincul arch region (39˚ S). The tectonic setting of the Neuquén basin, during the deposition of the Tordillo Formation, was controlled by the combined stresses generated by the subduction system to the west and the break-up of Pangea to the east. We propose that trench rollback in the Late Jurassic caused regional extension in the back arc zone. This stress field was locally modified by the clockwise rotation of South America due to the initial break-up of Pangea, that ended with the opening of the South Atlantic Ocean. This rotation produced a transpressive stress field in the southern Neuquén basin in which the strucures generated during the Permian collision of the Patagonia terrane were reactivated as strike-slip and reverse faults leading to variable basin geometries and subsidence patterns recorded by the Tordillo Formation in the north and south. Fil: Mescua, Jose Francisco. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina. Universidad Nacional de Cuyo. Facultad de Ciencias Exactas y Naturales; Argentina Fil: Suriano, Julieta. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, ...